Buddhism and comparative constitutional law - Ginsburg, Tom; Schonthal, Benjamin, 1976- (Comparative constitutional law and policy., 2023)
Buddhism and Comparative Constitutional Law offers the first comprehensive account of the entanglements of Buddhism and constitutional law in Sri Lanka, Myanmar, Thailand, Cambodia, Vietnam, Tibet, Bhutan, China, Mongolia, Korea, and Japan. Bringing together an interdisciplinary team of experts, the volume offers a complex portrait of "the Buddhist-constitutional complex," demonstrating the intricate and powerful ways in which Buddhist and constitutional ideas merged, interacted and co-evolved. The authors also highlight the important ways in which Buddhist actors have (re)conceived Western liberal ideals such as constitutionalism, rule of law, and secularism. Available Open Access on Cambridge Core, this trans-disciplinary volume is written to be accessible to a non-specialist audience.